2019
DOI: 10.1101/612325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laminin-driven Epac/Rap1 regulation of epithelial barriers on decellularized matrix

Abstract: Decellularized tissues offer a unique tool for developing regenerative biomaterials or in vitro platforms for the study of cell-extracellular matrix (ECM) interactions. One main challenge associated with decellularized lung tissue is that ECM components can be stripped away or altered by the detergents used to remove cellular debris. Without characterizing the composition of lung decellularized ECM (dECM) and the cellular response caused by the altered composition, it is difficult to utilize dECM for regenerat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…This study also shows short-term cell distribution over 3 days and, therefore, does not provide context for cell migration, proliferation, or differentiation. Extending the culture duration with the addition of recent bioreactor upgrades [Gilpin et al, 2014a;Nichols et al, 2014], scaffold pre-conditioning [Gilpin et al, 2017;Nichols et al, 2018;Young et al, 2019], multiple cell lineages and differentiation techniques [Ghaedi et al, 2014;Gilpin et al, 2014b;Stabler et al, 2016], and other practices for long-term tissue culture, this system can propel the study of more complex tissue transplantation challenges such as cellular differentiation, barrier integrity, longer-term function by starting with an efficient seeding mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also shows short-term cell distribution over 3 days and, therefore, does not provide context for cell migration, proliferation, or differentiation. Extending the culture duration with the addition of recent bioreactor upgrades [Gilpin et al, 2014a;Nichols et al, 2014], scaffold pre-conditioning [Gilpin et al, 2017;Nichols et al, 2018;Young et al, 2019], multiple cell lineages and differentiation techniques [Ghaedi et al, 2014;Gilpin et al, 2014b;Stabler et al, 2016], and other practices for long-term tissue culture, this system can propel the study of more complex tissue transplantation challenges such as cellular differentiation, barrier integrity, longer-term function by starting with an efficient seeding mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…MLE12 Cell Attachment Rate Assay 250,000 cells/cm 2 were seeded onto TCP coated with 0.1 mg/ mL porcine lung dECM prepared by protocols previously published by our laboratory [Link et al, 2017;Pouliot et al, 2016;Young et al, 2019Young et al, , 2020. Every 20 min for 4 h, unadhered cells and media were aspirated from a well and rinsed gently before fixation with 4% PFA.…”
Section: Cell Culturementioning
confidence: 99%
“…e ECM is the main structural component of the alveolar-capillary membrane, which not only plays a mechanical-supporting and mechanical-connecting role between cells but is also important in maintaining normal Evidence-Based Complementary and Alternative Medicine tissue structure and function [9,32,33]. Previous work has shown that ECM metabolic disorders are involved in the pathophysiological process of ALI and chronic lung injury [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, cells are in contact with each other not only directly through these adhesion proteins but also indirectly via the extracellular matrix, ECM, kind of an extracellular "glue," which includes proteins such as collagens, fibronectins, or laminins [89][90][91]. Various adhesion proteins such as cadherins, integrins, CAM (Cell Adhesion Molecules), selectins, etc., participate in these direct or indirect contacts between cell surfaces [92][93][94].…”
Section: Direct Interactions Between Membrane Proteinsmentioning
confidence: 99%